Calculated Choices in Policy-Making - De Vries, Michiel S. author. aut Link
XVI, 220 p.
Keywords: This is a book about making choices based on the evaluation of alternatives. The outcomes of choices are often worse than people expect. This book discusses the major problems in evaluating courses of action and examines the political contexts in which decisions are made. The subject matter of this book is at the crossroads of policy and research methodology. How can information derived from empirical research benefit a policy-maker or decision maker, and how should this information be incorporated in the decision-making process?